1997
DOI: 10.1046/j.1365-3040.1997.d01-39.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet‐B effects on transcript levels for photosynthetic genes are not mediated through carbohydrate metabolism

Abstract: The relationship between UV-B-induced changes in gene expression and carbohydrate levels in pea seedlings has been hivestigated. The effect of supplementary UV-B radiation on the transcript abundance for two photosynthetic genes, photosynthesis, respiration and the levels of carbohydrates was determined in fully expanded leaves of 17-dold pea seedlings nnder high (HL: 350 ^/mol m"^ s~') and low (LL: 150//mol m"^ s"') light. Supplementary UV-B eaused downregulation of the photosynthetic genes in green leaves un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 39 publications
2
8
0
Order By: Relevance
“…As UV-B radiation treated plants are known to have a tendency to have a lower sink capacity (Correia et al, 2000), the observed decreases in the C content of leaves induced by UV-B radiation indicate that the main response is mediated by a lower net photosynthetic rate. Similar results have been reported by Mackerness et al (1997). In our study, compared with the low altitude population, the high altitude population exhibited a higher biomass accumulation, water-use efficiency as well as ABA accumulation, as affected by enhanced UV-B radiation, which indicates that the high altitude population is more responsive to enhanced UV-B radiation.…”
Section: The Growth and Physiological Responses As Affected By Enhancsupporting
confidence: 91%
“…As UV-B radiation treated plants are known to have a tendency to have a lower sink capacity (Correia et al, 2000), the observed decreases in the C content of leaves induced by UV-B radiation indicate that the main response is mediated by a lower net photosynthetic rate. Similar results have been reported by Mackerness et al (1997). In our study, compared with the low altitude population, the high altitude population exhibited a higher biomass accumulation, water-use efficiency as well as ABA accumulation, as affected by enhanced UV-B radiation, which indicates that the high altitude population is more responsive to enhanced UV-B radiation.…”
Section: The Growth and Physiological Responses As Affected By Enhancsupporting
confidence: 91%
“…To date, few studies have evaluated the effects of UV-B radiation on plant carbohydrate or fiber content. Decreased available carbohydrate concentrations at elevated UV-B levels have been reported for glucose in pea (Mackerness et al 1997), sucrose in mulberry (Yazawa et al 1992), and soluble carbohydrates in Pinus (Katzel et al 1996). Gehrke et al (1995), working with leaf litter from Vaccinium uliginosum, reported no effect of UV-B dose on soluble carbohydrates, but observed a decrease in cellulose concentrations.…”
Section: Discussionmentioning
confidence: 91%
“…Indeed, ROS and plant hormones, SA, JA and ethylene have been shown to be key regulators of gene expression in response to UVB exposure. 122,[155][156][157] In plant responses to temperature stress, increase in ROS has been implicated. H 2 O 2 has been specifically involved in low temperature responses in plant.…”
Section: Seed Dormancymentioning
confidence: 99%